Reaching the Unreached Primary Teachers: Distance Teacher Education at the University of the South Pacific - Govinda Ishwar Lingham; Greg Burnett (Flexible Learning Association of New Zealand, 2012)
This paper reports on the recent completion of an educational aid project carried out at the regional University of the South Pacific in Fiji. From 2004 to 2006, the university's on-campus Bachelor of Education (primary) was restructured for delivery in flexible and distance learning mode, in order to better meet student need across the Pacific region. The paper highlights the processes as well as some of the challenges involved in such a large undertaking. The paper also highlights the unique distance/teacher education context in which the University of the South Pacific operates.